A new family of expectiles and its properties - Kuzmenko, V.M. (Кібернетика та комп’ютерні технології, 2020)
This paper considers a risk measure called expectile. We propose a new expression defining expectile, using maximization of CVaR by changing confidence level. This expression is specified for continuous and finite discrete distribution. It is proved that the optimal value of the confidence level is equal to the CDF of expectile value. We also consider a new family of expectiles defined by two parameters. Сomparison of different new expectiles with quantile for a set of distributions shows that proposed expectiles are closer to the quantile than the standard expectile. Two variants of expectile linearization are proposed and it is shown how to use them with linear loss function. Finally, we build three fundamental risk quadrangles where expectile is a statistic and risk. Мета роботи. Як правило, експектиль порівнюється із квантилем. Наша мета – порівняти експектиль із суперквантилем (CVaR), використовуючи однаковий параметр – рівень довіри. Для цього спочатку дається нове представлення експектиля через зважену суму середнього та CVaR. Потім розглядається нове сімейство експектилей, яке задається двома параметрами. Такі експектилі порівнюються з квантилем та CVaR для різних неперервних та скінчених дискретних розподілів. Ще одна мета – побудувати регулярний ризик-квадрат, де експектиль є функцією ризику. Цель работы. Как правило, экспектиль сравнивается с квантилем. Наша задача – сравнить экспектиль с суперквантилем (CVaR), используя одинаковый параметр – уровень доверия. Для этого мы сначала даем новое представление экспектиля через взвешенную сумму среднего и CVaR. Потом рассматриваем новое семейство экспектилей, которое задается двумя параметрами. Такие экспектили сравниваются с квантилем и CVaR для разных непрерывных и конечных дискретных распределений. Еще одна цель – построить регулярный риск-квадрат, где экспектиль является функцией риска.